Base and Prime Editing Technologies for Blood Disorders - Antoniou, Panagiotis; Miccio, Annarita; Brusson, Mégane (Frontiers in Genome Editing, 2021)
Nuclease-base genome editing strategies hold great promise for the treatment of blood disorders. However, a major drawback of these approaches is the generation of potentially harmful double strand breaks (DSBs). Base editing is a CRISPR-Cas9-based genome editing technology that allows the introduction of point mutations in the DNA without generating DSBs. Two major classes of base editors have been developed: cytidine base editors or CBEs allowing C>T conversions and adenine base editors or ABEs allowing A>G conversions. The scope of base editing tools has been extensively broadened, allowing higher efficiency, specificity, accessibility to previously inaccessible genetic loci and multiplexing, while maintaining a low rate of Insertions and Deletions (InDels). Base editing is a promising therapeutic strategy for genetic diseases caused by point mutations, such as many blood disorders and might be more effective than approaches based on homology-directed repair, which is moderately efficient in hematopoietic stem cells, the target cell population of many gene therapy approaches. In this review, we describe the development and evolution of the base editing system and its potential to correct blood disorders. We also discuss challenges of base editing approaches - including the delivery of base editors and the off-target events - and the advantages and disadvantages of base editing compared to classical genome editing strategies. Finally, we summarize the recent technologies that have further expanded the potential to correct genetic mutations, such as the novel base editing system allowing base transversions and the more versatile prime editing strategy.